Evaluating Oxidative Stress in Fibromyalgia: Diagnostic Utility and Its Relationship with Clinical and Psychological Parameters - Uslu, Emine Yildirim; Uslu, Muhammed Fuad; Yildiz, Sevler; Tabara, Muhammed Fatih (Mdpi, 2025)
Background and Objectives: This study aimed to evaluate the diagnostic value of oxidative stress parameters in fibromyalgia syndrome (FMS) and to investigate their potential associations with disease severity, functional impairment, anxiety, and depression. Materials and Methods: The study included 84 participants, consisting of 42 women diagnosed with fibromyalgia (FM) and 42 healthy female controls. Serum levels of total antioxidant status (TAS), total oxidant status (TOS), and malondialdehyde (MDA) were measured in all participants, and the oxidative stress index (OSI) was calculated. Additionally, the Fibromyalgia Impact Questionnaire (FIQ), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) were administered to assess mental health and functional status. Results: The levels of TOS, TAS, MDA, and the OSI were significantly higher in the fibromyalgia group compared to the control group (p < 0.001). The relationship between TAS, TOS, MDA, and OSI levels and BDI, BAI, and FIQ scale scores was investigated in the case group, but no significant associations were identified between oxidative stress markers and psychological or functional scores. When all participants were analyzed as a single group, significant correlations were found between TAS, TOS, MDA, and OSI levels and several biochemical parameters, including CRP, AST, free T4, HbA1c, ferritin, and folic acid. Conclusions: Our study adds to the growing body of evidence indicating elevated oxidative stress in female patients with fibromyalgia syndrome (FMS) and suggests that TAS, TOS, MDA, and OSI may serve as potential biomarkers for its diagnosis.
Keywords: fibromyalgia; total antioxidant status; total oxidant status